Optical And Microwave Technologies Select Proceedings of ICNETS2, Volume IV (Lecture Notes in Electrical Engineering, 2018)
This book gathers a collection of papers by international experts presented at the International Conference on NextGen Electronic Technologies (ICNETS2-2016). ICNETS2 encompasses six symposia covering all aspects of the electronics and communications domains, including relevant nano/micro materials and devices. Highlighting the latest research on Optical And Microwave Technologies, the book will benefit all researchers, professionals, and students working in the core areas of electronics and their applications, especially in signal processing, embedded systems, and networking.